### (0) Obligation:

Runtime Complexity TRS:
The TRS R consists of the following rules:

a__U11(tt, M, N) → a__U12(tt, M, N)
a__U12(tt, M, N) → s(a__plus(mark(N), mark(M)))
a__plus(N, 0) → mark(N)
a__plus(N, s(M)) → a__U11(tt, M, N)
mark(U11(X1, X2, X3)) → a__U11(mark(X1), X2, X3)
mark(U12(X1, X2, X3)) → a__U12(mark(X1), X2, X3)
mark(plus(X1, X2)) → a__plus(mark(X1), mark(X2))
mark(tt) → tt
mark(s(X)) → s(mark(X))
mark(0) → 0
a__U11(X1, X2, X3) → U11(X1, X2, X3)
a__U12(X1, X2, X3) → U12(X1, X2, X3)
a__plus(X1, X2) → plus(X1, X2)

Rewrite Strategy: FULL

### (1) DecreasingLoopProof (EQUIVALENT transformation)

The following loop(s) give(s) rise to the lower bound Ω(n1):
The rewrite sequence
a__U11(tt, M, U11(tt, X257_4, X358_4)) →+ s(a__plus(a__U11(tt, X257_4, X358_4), mark(M)))
gives rise to a decreasing loop by considering the right hand sides subterm at position [0,0].
The pumping substitution is [X358_4 / U11(tt, X257_4, X358_4)].
The result substitution is [M / X257_4].

### (3) RenamingProof (EQUIVALENT transformation)

Renamed function symbols to avoid clashes with predefined symbol.

### (4) Obligation:

Runtime Complexity Relative TRS:
The TRS R consists of the following rules:

a__U11(tt, M, N) → a__U12(tt, M, N)
a__U12(tt, M, N) → s(a__plus(mark(N), mark(M)))
a__plus(N, 0') → mark(N)
a__plus(N, s(M)) → a__U11(tt, M, N)
mark(U11(X1, X2, X3)) → a__U11(mark(X1), X2, X3)
mark(U12(X1, X2, X3)) → a__U12(mark(X1), X2, X3)
mark(plus(X1, X2)) → a__plus(mark(X1), mark(X2))
mark(tt) → tt
mark(s(X)) → s(mark(X))
mark(0') → 0'
a__U11(X1, X2, X3) → U11(X1, X2, X3)
a__U12(X1, X2, X3) → U12(X1, X2, X3)
a__plus(X1, X2) → plus(X1, X2)

S is empty.
Rewrite Strategy: FULL

Infered types.

### (6) Obligation:

TRS:
Rules:
a__U11(tt, M, N) → a__U12(tt, M, N)
a__U12(tt, M, N) → s(a__plus(mark(N), mark(M)))
a__plus(N, 0') → mark(N)
a__plus(N, s(M)) → a__U11(tt, M, N)
mark(U11(X1, X2, X3)) → a__U11(mark(X1), X2, X3)
mark(U12(X1, X2, X3)) → a__U12(mark(X1), X2, X3)
mark(plus(X1, X2)) → a__plus(mark(X1), mark(X2))
mark(tt) → tt
mark(s(X)) → s(mark(X))
mark(0') → 0'
a__U11(X1, X2, X3) → U11(X1, X2, X3)
a__U12(X1, X2, X3) → U12(X1, X2, X3)
a__plus(X1, X2) → plus(X1, X2)

Types:
a__U11 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
tt :: tt:s:0':U11:U12:plus
a__U12 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
s :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
a__plus :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
mark :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
0' :: tt:s:0':U11:U12:plus
U11 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
U12 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
plus :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
hole_tt:s:0':U11:U12:plus1_0 :: tt:s:0':U11:U12:plus
gen_tt:s:0':U11:U12:plus2_0 :: Nat → tt:s:0':U11:U12:plus

### (7) OrderProof (LOWER BOUND(ID) transformation)

Heuristically decided to analyse the following defined symbols:
a__U11, a__U12, a__plus, mark

They will be analysed ascendingly in the following order:
a__U11 = a__U12
a__U11 = a__plus
a__U11 = mark
a__U12 = a__plus
a__U12 = mark
a__plus = mark

### (8) Obligation:

TRS:
Rules:
a__U11(tt, M, N) → a__U12(tt, M, N)
a__U12(tt, M, N) → s(a__plus(mark(N), mark(M)))
a__plus(N, 0') → mark(N)
a__plus(N, s(M)) → a__U11(tt, M, N)
mark(U11(X1, X2, X3)) → a__U11(mark(X1), X2, X3)
mark(U12(X1, X2, X3)) → a__U12(mark(X1), X2, X3)
mark(plus(X1, X2)) → a__plus(mark(X1), mark(X2))
mark(tt) → tt
mark(s(X)) → s(mark(X))
mark(0') → 0'
a__U11(X1, X2, X3) → U11(X1, X2, X3)
a__U12(X1, X2, X3) → U12(X1, X2, X3)
a__plus(X1, X2) → plus(X1, X2)

Types:
a__U11 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
tt :: tt:s:0':U11:U12:plus
a__U12 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
s :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
a__plus :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
mark :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
0' :: tt:s:0':U11:U12:plus
U11 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
U12 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
plus :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
hole_tt:s:0':U11:U12:plus1_0 :: tt:s:0':U11:U12:plus
gen_tt:s:0':U11:U12:plus2_0 :: Nat → tt:s:0':U11:U12:plus

Generator Equations:
gen_tt:s:0':U11:U12:plus2_0(0) ⇔ tt
gen_tt:s:0':U11:U12:plus2_0(+(x, 1)) ⇔ s(gen_tt:s:0':U11:U12:plus2_0(x))

The following defined symbols remain to be analysed:
a__U12, a__U11, a__plus, mark

They will be analysed ascendingly in the following order:
a__U11 = a__U12
a__U11 = a__plus
a__U11 = mark
a__U12 = a__plus
a__U12 = mark
a__plus = mark

### (9) NoRewriteLemmaProof (LOWER BOUND(ID) transformation)

Could not prove a rewrite lemma for the defined symbol a__U12.

### (10) Obligation:

TRS:
Rules:
a__U11(tt, M, N) → a__U12(tt, M, N)
a__U12(tt, M, N) → s(a__plus(mark(N), mark(M)))
a__plus(N, 0') → mark(N)
a__plus(N, s(M)) → a__U11(tt, M, N)
mark(U11(X1, X2, X3)) → a__U11(mark(X1), X2, X3)
mark(U12(X1, X2, X3)) → a__U12(mark(X1), X2, X3)
mark(plus(X1, X2)) → a__plus(mark(X1), mark(X2))
mark(tt) → tt
mark(s(X)) → s(mark(X))
mark(0') → 0'
a__U11(X1, X2, X3) → U11(X1, X2, X3)
a__U12(X1, X2, X3) → U12(X1, X2, X3)
a__plus(X1, X2) → plus(X1, X2)

Types:
a__U11 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
tt :: tt:s:0':U11:U12:plus
a__U12 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
s :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
a__plus :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
mark :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
0' :: tt:s:0':U11:U12:plus
U11 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
U12 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
plus :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
hole_tt:s:0':U11:U12:plus1_0 :: tt:s:0':U11:U12:plus
gen_tt:s:0':U11:U12:plus2_0 :: Nat → tt:s:0':U11:U12:plus

Generator Equations:
gen_tt:s:0':U11:U12:plus2_0(0) ⇔ tt
gen_tt:s:0':U11:U12:plus2_0(+(x, 1)) ⇔ s(gen_tt:s:0':U11:U12:plus2_0(x))

The following defined symbols remain to be analysed:
a__plus, a__U11, mark

They will be analysed ascendingly in the following order:
a__U11 = a__U12
a__U11 = a__plus
a__U11 = mark
a__U12 = a__plus
a__U12 = mark
a__plus = mark

### (11) NoRewriteLemmaProof (LOWER BOUND(ID) transformation)

Could not prove a rewrite lemma for the defined symbol a__plus.

### (12) Obligation:

TRS:
Rules:
a__U11(tt, M, N) → a__U12(tt, M, N)
a__U12(tt, M, N) → s(a__plus(mark(N), mark(M)))
a__plus(N, 0') → mark(N)
a__plus(N, s(M)) → a__U11(tt, M, N)
mark(U11(X1, X2, X3)) → a__U11(mark(X1), X2, X3)
mark(U12(X1, X2, X3)) → a__U12(mark(X1), X2, X3)
mark(plus(X1, X2)) → a__plus(mark(X1), mark(X2))
mark(tt) → tt
mark(s(X)) → s(mark(X))
mark(0') → 0'
a__U11(X1, X2, X3) → U11(X1, X2, X3)
a__U12(X1, X2, X3) → U12(X1, X2, X3)
a__plus(X1, X2) → plus(X1, X2)

Types:
a__U11 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
tt :: tt:s:0':U11:U12:plus
a__U12 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
s :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
a__plus :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
mark :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
0' :: tt:s:0':U11:U12:plus
U11 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
U12 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
plus :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
hole_tt:s:0':U11:U12:plus1_0 :: tt:s:0':U11:U12:plus
gen_tt:s:0':U11:U12:plus2_0 :: Nat → tt:s:0':U11:U12:plus

Generator Equations:
gen_tt:s:0':U11:U12:plus2_0(0) ⇔ tt
gen_tt:s:0':U11:U12:plus2_0(+(x, 1)) ⇔ s(gen_tt:s:0':U11:U12:plus2_0(x))

The following defined symbols remain to be analysed:
mark, a__U11

They will be analysed ascendingly in the following order:
a__U11 = a__U12
a__U11 = a__plus
a__U11 = mark
a__U12 = a__plus
a__U12 = mark
a__plus = mark

### (13) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
mark(gen_tt:s:0':U11:U12:plus2_0(n7802_0)) → gen_tt:s:0':U11:U12:plus2_0(n7802_0), rt ∈ Ω(1 + n78020)

Induction Base:
mark(gen_tt:s:0':U11:U12:plus2_0(0)) →RΩ(1)
tt

Induction Step:
mark(gen_tt:s:0':U11:U12:plus2_0(+(n7802_0, 1))) →RΩ(1)
s(mark(gen_tt:s:0':U11:U12:plus2_0(n7802_0))) →IH
s(gen_tt:s:0':U11:U12:plus2_0(c7803_0))

We have rt ∈ Ω(n1) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

### (15) Obligation:

TRS:
Rules:
a__U11(tt, M, N) → a__U12(tt, M, N)
a__U12(tt, M, N) → s(a__plus(mark(N), mark(M)))
a__plus(N, 0') → mark(N)
a__plus(N, s(M)) → a__U11(tt, M, N)
mark(U11(X1, X2, X3)) → a__U11(mark(X1), X2, X3)
mark(U12(X1, X2, X3)) → a__U12(mark(X1), X2, X3)
mark(plus(X1, X2)) → a__plus(mark(X1), mark(X2))
mark(tt) → tt
mark(s(X)) → s(mark(X))
mark(0') → 0'
a__U11(X1, X2, X3) → U11(X1, X2, X3)
a__U12(X1, X2, X3) → U12(X1, X2, X3)
a__plus(X1, X2) → plus(X1, X2)

Types:
a__U11 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
tt :: tt:s:0':U11:U12:plus
a__U12 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
s :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
a__plus :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
mark :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
0' :: tt:s:0':U11:U12:plus
U11 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
U12 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
plus :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
hole_tt:s:0':U11:U12:plus1_0 :: tt:s:0':U11:U12:plus
gen_tt:s:0':U11:U12:plus2_0 :: Nat → tt:s:0':U11:U12:plus

Lemmas:
mark(gen_tt:s:0':U11:U12:plus2_0(n7802_0)) → gen_tt:s:0':U11:U12:plus2_0(n7802_0), rt ∈ Ω(1 + n78020)

Generator Equations:
gen_tt:s:0':U11:U12:plus2_0(0) ⇔ tt
gen_tt:s:0':U11:U12:plus2_0(+(x, 1)) ⇔ s(gen_tt:s:0':U11:U12:plus2_0(x))

The following defined symbols remain to be analysed:
a__U11, a__U12, a__plus

They will be analysed ascendingly in the following order:
a__U11 = a__U12
a__U11 = a__plus
a__U11 = mark
a__U12 = a__plus
a__U12 = mark
a__plus = mark

### (16) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
a__U11(gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(n8498_0), gen_tt:s:0':U11:U12:plus2_0(c)) → *3_0, rt ∈ Ω(c·n84980 + n84980 + n849802)

Induction Base:
a__U11(gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(c))

Induction Step:
a__U11(gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(+(n8498_0, 1)), gen_tt:s:0':U11:U12:plus2_0(c)) →RΩ(1)
a__U12(tt, gen_tt:s:0':U11:U12:plus2_0(+(n8498_0, 1)), gen_tt:s:0':U11:U12:plus2_0(c)) →RΩ(1)
s(a__plus(mark(gen_tt:s:0':U11:U12:plus2_0(c)), mark(gen_tt:s:0':U11:U12:plus2_0(+(1, n8498_0))))) →LΩ(1 + c)
s(a__plus(gen_tt:s:0':U11:U12:plus2_0(c), mark(gen_tt:s:0':U11:U12:plus2_0(+(1, n8498_0))))) →LΩ(2 + n84980)
s(a__plus(gen_tt:s:0':U11:U12:plus2_0(c), gen_tt:s:0':U11:U12:plus2_0(+(1, n8498_0)))) →RΩ(1)
s(a__U11(tt, gen_tt:s:0':U11:U12:plus2_0(n8498_0), gen_tt:s:0':U11:U12:plus2_0(c))) →IH
s(*3_0)

We have rt ∈ Ω(n2) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n2).

### (18) Obligation:

TRS:
Rules:
a__U11(tt, M, N) → a__U12(tt, M, N)
a__U12(tt, M, N) → s(a__plus(mark(N), mark(M)))
a__plus(N, 0') → mark(N)
a__plus(N, s(M)) → a__U11(tt, M, N)
mark(U11(X1, X2, X3)) → a__U11(mark(X1), X2, X3)
mark(U12(X1, X2, X3)) → a__U12(mark(X1), X2, X3)
mark(plus(X1, X2)) → a__plus(mark(X1), mark(X2))
mark(tt) → tt
mark(s(X)) → s(mark(X))
mark(0') → 0'
a__U11(X1, X2, X3) → U11(X1, X2, X3)
a__U12(X1, X2, X3) → U12(X1, X2, X3)
a__plus(X1, X2) → plus(X1, X2)

Types:
a__U11 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
tt :: tt:s:0':U11:U12:plus
a__U12 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
s :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
a__plus :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
mark :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
0' :: tt:s:0':U11:U12:plus
U11 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
U12 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
plus :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
hole_tt:s:0':U11:U12:plus1_0 :: tt:s:0':U11:U12:plus
gen_tt:s:0':U11:U12:plus2_0 :: Nat → tt:s:0':U11:U12:plus

Lemmas:
mark(gen_tt:s:0':U11:U12:plus2_0(n7802_0)) → gen_tt:s:0':U11:U12:plus2_0(n7802_0), rt ∈ Ω(1 + n78020)
a__U11(gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(n8498_0), gen_tt:s:0':U11:U12:plus2_0(c)) → *3_0, rt ∈ Ω(c·n84980 + n84980 + n849802)

Generator Equations:
gen_tt:s:0':U11:U12:plus2_0(0) ⇔ tt
gen_tt:s:0':U11:U12:plus2_0(+(x, 1)) ⇔ s(gen_tt:s:0':U11:U12:plus2_0(x))

The following defined symbols remain to be analysed:
a__U12, a__plus, mark

They will be analysed ascendingly in the following order:
a__U11 = a__U12
a__U11 = a__plus
a__U11 = mark
a__U12 = a__plus
a__U12 = mark
a__plus = mark

### (19) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
a__U12(gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(n10562_0), gen_tt:s:0':U11:U12:plus2_0(c)) → *3_0, rt ∈ Ω(c·n105620 + n105620 + n1056202)

Induction Base:
a__U12(gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(c))

Induction Step:
a__U12(gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(+(n10562_0, 1)), gen_tt:s:0':U11:U12:plus2_0(c)) →RΩ(1)
s(a__plus(mark(gen_tt:s:0':U11:U12:plus2_0(c)), mark(gen_tt:s:0':U11:U12:plus2_0(+(n10562_0, 1))))) →LΩ(1 + c)
s(a__plus(gen_tt:s:0':U11:U12:plus2_0(c), mark(gen_tt:s:0':U11:U12:plus2_0(+(1, n10562_0))))) →LΩ(2 + n105620)
s(a__plus(gen_tt:s:0':U11:U12:plus2_0(c), gen_tt:s:0':U11:U12:plus2_0(+(1, n10562_0)))) →RΩ(1)
s(a__U11(tt, gen_tt:s:0':U11:U12:plus2_0(n10562_0), gen_tt:s:0':U11:U12:plus2_0(c))) →RΩ(1)
s(a__U12(tt, gen_tt:s:0':U11:U12:plus2_0(n10562_0), gen_tt:s:0':U11:U12:plus2_0(c))) →IH
s(*3_0)

We have rt ∈ Ω(n2) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n2).

### (21) Obligation:

TRS:
Rules:
a__U11(tt, M, N) → a__U12(tt, M, N)
a__U12(tt, M, N) → s(a__plus(mark(N), mark(M)))
a__plus(N, 0') → mark(N)
a__plus(N, s(M)) → a__U11(tt, M, N)
mark(U11(X1, X2, X3)) → a__U11(mark(X1), X2, X3)
mark(U12(X1, X2, X3)) → a__U12(mark(X1), X2, X3)
mark(plus(X1, X2)) → a__plus(mark(X1), mark(X2))
mark(tt) → tt
mark(s(X)) → s(mark(X))
mark(0') → 0'
a__U11(X1, X2, X3) → U11(X1, X2, X3)
a__U12(X1, X2, X3) → U12(X1, X2, X3)
a__plus(X1, X2) → plus(X1, X2)

Types:
a__U11 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
tt :: tt:s:0':U11:U12:plus
a__U12 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
s :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
a__plus :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
mark :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
0' :: tt:s:0':U11:U12:plus
U11 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
U12 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
plus :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
hole_tt:s:0':U11:U12:plus1_0 :: tt:s:0':U11:U12:plus
gen_tt:s:0':U11:U12:plus2_0 :: Nat → tt:s:0':U11:U12:plus

Lemmas:
mark(gen_tt:s:0':U11:U12:plus2_0(n7802_0)) → gen_tt:s:0':U11:U12:plus2_0(n7802_0), rt ∈ Ω(1 + n78020)
a__U11(gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(n8498_0), gen_tt:s:0':U11:U12:plus2_0(c)) → *3_0, rt ∈ Ω(c·n84980 + n84980 + n849802)
a__U12(gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(n10562_0), gen_tt:s:0':U11:U12:plus2_0(c)) → *3_0, rt ∈ Ω(c·n105620 + n105620 + n1056202)

Generator Equations:
gen_tt:s:0':U11:U12:plus2_0(0) ⇔ tt
gen_tt:s:0':U11:U12:plus2_0(+(x, 1)) ⇔ s(gen_tt:s:0':U11:U12:plus2_0(x))

The following defined symbols remain to be analysed:
a__plus, a__U11, mark

They will be analysed ascendingly in the following order:
a__U11 = a__U12
a__U11 = a__plus
a__U11 = mark
a__U12 = a__plus
a__U12 = mark
a__plus = mark

### (22) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
a__plus(gen_tt:s:0':U11:U12:plus2_0(a), gen_tt:s:0':U11:U12:plus2_0(+(1, n12888_0))) → *3_0, rt ∈ Ω(a·n128880 + n128880 + n1288802)

Induction Base:
a__plus(gen_tt:s:0':U11:U12:plus2_0(a), gen_tt:s:0':U11:U12:plus2_0(+(1, 0)))

Induction Step:
a__plus(gen_tt:s:0':U11:U12:plus2_0(a), gen_tt:s:0':U11:U12:plus2_0(+(1, +(n12888_0, 1)))) →RΩ(1)
a__U11(tt, gen_tt:s:0':U11:U12:plus2_0(+(1, n12888_0)), gen_tt:s:0':U11:U12:plus2_0(a)) →RΩ(1)
a__U12(tt, gen_tt:s:0':U11:U12:plus2_0(+(1, n12888_0)), gen_tt:s:0':U11:U12:plus2_0(a)) →RΩ(1)
s(a__plus(mark(gen_tt:s:0':U11:U12:plus2_0(a)), mark(gen_tt:s:0':U11:U12:plus2_0(+(1, n12888_0))))) →LΩ(1 + a)
s(a__plus(gen_tt:s:0':U11:U12:plus2_0(a), mark(gen_tt:s:0':U11:U12:plus2_0(+(1, n12888_0))))) →LΩ(2 + n128880)
s(a__plus(gen_tt:s:0':U11:U12:plus2_0(a), gen_tt:s:0':U11:U12:plus2_0(+(1, n12888_0)))) →IH
s(*3_0)

We have rt ∈ Ω(n2) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n2).

### (24) Obligation:

TRS:
Rules:
a__U11(tt, M, N) → a__U12(tt, M, N)
a__U12(tt, M, N) → s(a__plus(mark(N), mark(M)))
a__plus(N, 0') → mark(N)
a__plus(N, s(M)) → a__U11(tt, M, N)
mark(U11(X1, X2, X3)) → a__U11(mark(X1), X2, X3)
mark(U12(X1, X2, X3)) → a__U12(mark(X1), X2, X3)
mark(plus(X1, X2)) → a__plus(mark(X1), mark(X2))
mark(tt) → tt
mark(s(X)) → s(mark(X))
mark(0') → 0'
a__U11(X1, X2, X3) → U11(X1, X2, X3)
a__U12(X1, X2, X3) → U12(X1, X2, X3)
a__plus(X1, X2) → plus(X1, X2)

Types:
a__U11 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
tt :: tt:s:0':U11:U12:plus
a__U12 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
s :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
a__plus :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
mark :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
0' :: tt:s:0':U11:U12:plus
U11 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
U12 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
plus :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
hole_tt:s:0':U11:U12:plus1_0 :: tt:s:0':U11:U12:plus
gen_tt:s:0':U11:U12:plus2_0 :: Nat → tt:s:0':U11:U12:plus

Lemmas:
mark(gen_tt:s:0':U11:U12:plus2_0(n7802_0)) → gen_tt:s:0':U11:U12:plus2_0(n7802_0), rt ∈ Ω(1 + n78020)
a__U11(gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(n8498_0), gen_tt:s:0':U11:U12:plus2_0(c)) → *3_0, rt ∈ Ω(c·n84980 + n84980 + n849802)
a__U12(gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(n10562_0), gen_tt:s:0':U11:U12:plus2_0(c)) → *3_0, rt ∈ Ω(c·n105620 + n105620 + n1056202)
a__plus(gen_tt:s:0':U11:U12:plus2_0(a), gen_tt:s:0':U11:U12:plus2_0(+(1, n12888_0))) → *3_0, rt ∈ Ω(a·n128880 + n128880 + n1288802)

Generator Equations:
gen_tt:s:0':U11:U12:plus2_0(0) ⇔ tt
gen_tt:s:0':U11:U12:plus2_0(+(x, 1)) ⇔ s(gen_tt:s:0':U11:U12:plus2_0(x))

The following defined symbols remain to be analysed:
mark, a__U11, a__U12

They will be analysed ascendingly in the following order:
a__U11 = a__U12
a__U11 = a__plus
a__U11 = mark
a__U12 = a__plus
a__U12 = mark
a__plus = mark

### (25) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
mark(gen_tt:s:0':U11:U12:plus2_0(n15871_0)) → gen_tt:s:0':U11:U12:plus2_0(n15871_0), rt ∈ Ω(1 + n158710)

Induction Base:
mark(gen_tt:s:0':U11:U12:plus2_0(0)) →RΩ(1)
tt

Induction Step:
mark(gen_tt:s:0':U11:U12:plus2_0(+(n15871_0, 1))) →RΩ(1)
s(mark(gen_tt:s:0':U11:U12:plus2_0(n15871_0))) →IH
s(gen_tt:s:0':U11:U12:plus2_0(c15872_0))

We have rt ∈ Ω(n1) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

### (27) Obligation:

TRS:
Rules:
a__U11(tt, M, N) → a__U12(tt, M, N)
a__U12(tt, M, N) → s(a__plus(mark(N), mark(M)))
a__plus(N, 0') → mark(N)
a__plus(N, s(M)) → a__U11(tt, M, N)
mark(U11(X1, X2, X3)) → a__U11(mark(X1), X2, X3)
mark(U12(X1, X2, X3)) → a__U12(mark(X1), X2, X3)
mark(plus(X1, X2)) → a__plus(mark(X1), mark(X2))
mark(tt) → tt
mark(s(X)) → s(mark(X))
mark(0') → 0'
a__U11(X1, X2, X3) → U11(X1, X2, X3)
a__U12(X1, X2, X3) → U12(X1, X2, X3)
a__plus(X1, X2) → plus(X1, X2)

Types:
a__U11 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
tt :: tt:s:0':U11:U12:plus
a__U12 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
s :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
a__plus :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
mark :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
0' :: tt:s:0':U11:U12:plus
U11 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
U12 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
plus :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
hole_tt:s:0':U11:U12:plus1_0 :: tt:s:0':U11:U12:plus
gen_tt:s:0':U11:U12:plus2_0 :: Nat → tt:s:0':U11:U12:plus

Lemmas:
mark(gen_tt:s:0':U11:U12:plus2_0(n15871_0)) → gen_tt:s:0':U11:U12:plus2_0(n15871_0), rt ∈ Ω(1 + n158710)
a__U11(gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(n8498_0), gen_tt:s:0':U11:U12:plus2_0(c)) → *3_0, rt ∈ Ω(c·n84980 + n84980 + n849802)
a__U12(gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(n10562_0), gen_tt:s:0':U11:U12:plus2_0(c)) → *3_0, rt ∈ Ω(c·n105620 + n105620 + n1056202)
a__plus(gen_tt:s:0':U11:U12:plus2_0(a), gen_tt:s:0':U11:U12:plus2_0(+(1, n12888_0))) → *3_0, rt ∈ Ω(a·n128880 + n128880 + n1288802)

Generator Equations:
gen_tt:s:0':U11:U12:plus2_0(0) ⇔ tt
gen_tt:s:0':U11:U12:plus2_0(+(x, 1)) ⇔ s(gen_tt:s:0':U11:U12:plus2_0(x))

The following defined symbols remain to be analysed:
a__U11, a__U12

They will be analysed ascendingly in the following order:
a__U11 = a__U12
a__U11 = a__plus
a__U11 = mark
a__U12 = a__plus
a__U12 = mark
a__plus = mark

### (28) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
a__U11(gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(n16876_0), gen_tt:s:0':U11:U12:plus2_0(c)) → *3_0, rt ∈ Ω(c·n168760 + n168760 + n1687602)

Induction Base:
a__U11(gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(c))

Induction Step:
a__U11(gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(+(n16876_0, 1)), gen_tt:s:0':U11:U12:plus2_0(c)) →RΩ(1)
a__U12(tt, gen_tt:s:0':U11:U12:plus2_0(+(n16876_0, 1)), gen_tt:s:0':U11:U12:plus2_0(c)) →RΩ(1)
s(a__plus(mark(gen_tt:s:0':U11:U12:plus2_0(c)), mark(gen_tt:s:0':U11:U12:plus2_0(+(1, n16876_0))))) →LΩ(1 + c)
s(a__plus(gen_tt:s:0':U11:U12:plus2_0(c), mark(gen_tt:s:0':U11:U12:plus2_0(+(1, n16876_0))))) →LΩ(2 + n168760)
s(a__plus(gen_tt:s:0':U11:U12:plus2_0(c), gen_tt:s:0':U11:U12:plus2_0(+(1, n16876_0)))) →RΩ(1)
s(a__U11(tt, gen_tt:s:0':U11:U12:plus2_0(n16876_0), gen_tt:s:0':U11:U12:plus2_0(c))) →IH
s(*3_0)

We have rt ∈ Ω(n2) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n2).

### (30) Obligation:

TRS:
Rules:
a__U11(tt, M, N) → a__U12(tt, M, N)
a__U12(tt, M, N) → s(a__plus(mark(N), mark(M)))
a__plus(N, 0') → mark(N)
a__plus(N, s(M)) → a__U11(tt, M, N)
mark(U11(X1, X2, X3)) → a__U11(mark(X1), X2, X3)
mark(U12(X1, X2, X3)) → a__U12(mark(X1), X2, X3)
mark(plus(X1, X2)) → a__plus(mark(X1), mark(X2))
mark(tt) → tt
mark(s(X)) → s(mark(X))
mark(0') → 0'
a__U11(X1, X2, X3) → U11(X1, X2, X3)
a__U12(X1, X2, X3) → U12(X1, X2, X3)
a__plus(X1, X2) → plus(X1, X2)

Types:
a__U11 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
tt :: tt:s:0':U11:U12:plus
a__U12 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
s :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
a__plus :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
mark :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
0' :: tt:s:0':U11:U12:plus
U11 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
U12 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
plus :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
hole_tt:s:0':U11:U12:plus1_0 :: tt:s:0':U11:U12:plus
gen_tt:s:0':U11:U12:plus2_0 :: Nat → tt:s:0':U11:U12:plus

Lemmas:
mark(gen_tt:s:0':U11:U12:plus2_0(n15871_0)) → gen_tt:s:0':U11:U12:plus2_0(n15871_0), rt ∈ Ω(1 + n158710)
a__U11(gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(n16876_0), gen_tt:s:0':U11:U12:plus2_0(c)) → *3_0, rt ∈ Ω(c·n168760 + n168760 + n1687602)
a__U12(gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(n10562_0), gen_tt:s:0':U11:U12:plus2_0(c)) → *3_0, rt ∈ Ω(c·n105620 + n105620 + n1056202)
a__plus(gen_tt:s:0':U11:U12:plus2_0(a), gen_tt:s:0':U11:U12:plus2_0(+(1, n12888_0))) → *3_0, rt ∈ Ω(a·n128880 + n128880 + n1288802)

Generator Equations:
gen_tt:s:0':U11:U12:plus2_0(0) ⇔ tt
gen_tt:s:0':U11:U12:plus2_0(+(x, 1)) ⇔ s(gen_tt:s:0':U11:U12:plus2_0(x))

The following defined symbols remain to be analysed:
a__U12

They will be analysed ascendingly in the following order:
a__U11 = a__U12
a__U11 = a__plus
a__U11 = mark
a__U12 = a__plus
a__U12 = mark
a__plus = mark

### (31) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
a__U12(gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(n20155_0), gen_tt:s:0':U11:U12:plus2_0(c)) → *3_0, rt ∈ Ω(c·n201550 + n201550 + n2015502)

Induction Base:
a__U12(gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(c))

Induction Step:
a__U12(gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(+(n20155_0, 1)), gen_tt:s:0':U11:U12:plus2_0(c)) →RΩ(1)
s(a__plus(mark(gen_tt:s:0':U11:U12:plus2_0(c)), mark(gen_tt:s:0':U11:U12:plus2_0(+(n20155_0, 1))))) →LΩ(1 + c)
s(a__plus(gen_tt:s:0':U11:U12:plus2_0(c), mark(gen_tt:s:0':U11:U12:plus2_0(+(1, n20155_0))))) →LΩ(2 + n201550)
s(a__plus(gen_tt:s:0':U11:U12:plus2_0(c), gen_tt:s:0':U11:U12:plus2_0(+(1, n20155_0)))) →RΩ(1)
s(a__U11(tt, gen_tt:s:0':U11:U12:plus2_0(n20155_0), gen_tt:s:0':U11:U12:plus2_0(c))) →RΩ(1)
s(a__U12(tt, gen_tt:s:0':U11:U12:plus2_0(n20155_0), gen_tt:s:0':U11:U12:plus2_0(c))) →IH
s(*3_0)

We have rt ∈ Ω(n2) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n2).

### (33) Obligation:

TRS:
Rules:
a__U11(tt, M, N) → a__U12(tt, M, N)
a__U12(tt, M, N) → s(a__plus(mark(N), mark(M)))
a__plus(N, 0') → mark(N)
a__plus(N, s(M)) → a__U11(tt, M, N)
mark(U11(X1, X2, X3)) → a__U11(mark(X1), X2, X3)
mark(U12(X1, X2, X3)) → a__U12(mark(X1), X2, X3)
mark(plus(X1, X2)) → a__plus(mark(X1), mark(X2))
mark(tt) → tt
mark(s(X)) → s(mark(X))
mark(0') → 0'
a__U11(X1, X2, X3) → U11(X1, X2, X3)
a__U12(X1, X2, X3) → U12(X1, X2, X3)
a__plus(X1, X2) → plus(X1, X2)

Types:
a__U11 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
tt :: tt:s:0':U11:U12:plus
a__U12 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
s :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
a__plus :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
mark :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
0' :: tt:s:0':U11:U12:plus
U11 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
U12 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
plus :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
hole_tt:s:0':U11:U12:plus1_0 :: tt:s:0':U11:U12:plus
gen_tt:s:0':U11:U12:plus2_0 :: Nat → tt:s:0':U11:U12:plus

Lemmas:
mark(gen_tt:s:0':U11:U12:plus2_0(n15871_0)) → gen_tt:s:0':U11:U12:plus2_0(n15871_0), rt ∈ Ω(1 + n158710)
a__U11(gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(n16876_0), gen_tt:s:0':U11:U12:plus2_0(c)) → *3_0, rt ∈ Ω(c·n168760 + n168760 + n1687602)
a__U12(gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(n20155_0), gen_tt:s:0':U11:U12:plus2_0(c)) → *3_0, rt ∈ Ω(c·n201550 + n201550 + n2015502)
a__plus(gen_tt:s:0':U11:U12:plus2_0(a), gen_tt:s:0':U11:U12:plus2_0(+(1, n12888_0))) → *3_0, rt ∈ Ω(a·n128880 + n128880 + n1288802)

Generator Equations:
gen_tt:s:0':U11:U12:plus2_0(0) ⇔ tt
gen_tt:s:0':U11:U12:plus2_0(+(x, 1)) ⇔ s(gen_tt:s:0':U11:U12:plus2_0(x))

No more defined symbols left to analyse.

### (34) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n2) was proven with the following lemma:
a__U11(gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(n16876_0), gen_tt:s:0':U11:U12:plus2_0(c)) → *3_0, rt ∈ Ω(c·n168760 + n168760 + n1687602)

### (36) Obligation:

TRS:
Rules:
a__U11(tt, M, N) → a__U12(tt, M, N)
a__U12(tt, M, N) → s(a__plus(mark(N), mark(M)))
a__plus(N, 0') → mark(N)
a__plus(N, s(M)) → a__U11(tt, M, N)
mark(U11(X1, X2, X3)) → a__U11(mark(X1), X2, X3)
mark(U12(X1, X2, X3)) → a__U12(mark(X1), X2, X3)
mark(plus(X1, X2)) → a__plus(mark(X1), mark(X2))
mark(tt) → tt
mark(s(X)) → s(mark(X))
mark(0') → 0'
a__U11(X1, X2, X3) → U11(X1, X2, X3)
a__U12(X1, X2, X3) → U12(X1, X2, X3)
a__plus(X1, X2) → plus(X1, X2)

Types:
a__U11 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
tt :: tt:s:0':U11:U12:plus
a__U12 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
s :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
a__plus :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
mark :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
0' :: tt:s:0':U11:U12:plus
U11 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
U12 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
plus :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
hole_tt:s:0':U11:U12:plus1_0 :: tt:s:0':U11:U12:plus
gen_tt:s:0':U11:U12:plus2_0 :: Nat → tt:s:0':U11:U12:plus

Lemmas:
mark(gen_tt:s:0':U11:U12:plus2_0(n15871_0)) → gen_tt:s:0':U11:U12:plus2_0(n15871_0), rt ∈ Ω(1 + n158710)
a__U11(gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(n16876_0), gen_tt:s:0':U11:U12:plus2_0(c)) → *3_0, rt ∈ Ω(c·n168760 + n168760 + n1687602)
a__U12(gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(n20155_0), gen_tt:s:0':U11:U12:plus2_0(c)) → *3_0, rt ∈ Ω(c·n201550 + n201550 + n2015502)
a__plus(gen_tt:s:0':U11:U12:plus2_0(a), gen_tt:s:0':U11:U12:plus2_0(+(1, n12888_0))) → *3_0, rt ∈ Ω(a·n128880 + n128880 + n1288802)

Generator Equations:
gen_tt:s:0':U11:U12:plus2_0(0) ⇔ tt
gen_tt:s:0':U11:U12:plus2_0(+(x, 1)) ⇔ s(gen_tt:s:0':U11:U12:plus2_0(x))

No more defined symbols left to analyse.

### (37) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n2) was proven with the following lemma:
a__U11(gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(n16876_0), gen_tt:s:0':U11:U12:plus2_0(c)) → *3_0, rt ∈ Ω(c·n168760 + n168760 + n1687602)

### (39) Obligation:

TRS:
Rules:
a__U11(tt, M, N) → a__U12(tt, M, N)
a__U12(tt, M, N) → s(a__plus(mark(N), mark(M)))
a__plus(N, 0') → mark(N)
a__plus(N, s(M)) → a__U11(tt, M, N)
mark(U11(X1, X2, X3)) → a__U11(mark(X1), X2, X3)
mark(U12(X1, X2, X3)) → a__U12(mark(X1), X2, X3)
mark(plus(X1, X2)) → a__plus(mark(X1), mark(X2))
mark(tt) → tt
mark(s(X)) → s(mark(X))
mark(0') → 0'
a__U11(X1, X2, X3) → U11(X1, X2, X3)
a__U12(X1, X2, X3) → U12(X1, X2, X3)
a__plus(X1, X2) → plus(X1, X2)

Types:
a__U11 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
tt :: tt:s:0':U11:U12:plus
a__U12 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
s :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
a__plus :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
mark :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
0' :: tt:s:0':U11:U12:plus
U11 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
U12 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
plus :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
hole_tt:s:0':U11:U12:plus1_0 :: tt:s:0':U11:U12:plus
gen_tt:s:0':U11:U12:plus2_0 :: Nat → tt:s:0':U11:U12:plus

Lemmas:
mark(gen_tt:s:0':U11:U12:plus2_0(n15871_0)) → gen_tt:s:0':U11:U12:plus2_0(n15871_0), rt ∈ Ω(1 + n158710)
a__U11(gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(n16876_0), gen_tt:s:0':U11:U12:plus2_0(c)) → *3_0, rt ∈ Ω(c·n168760 + n168760 + n1687602)
a__U12(gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(n10562_0), gen_tt:s:0':U11:U12:plus2_0(c)) → *3_0, rt ∈ Ω(c·n105620 + n105620 + n1056202)
a__plus(gen_tt:s:0':U11:U12:plus2_0(a), gen_tt:s:0':U11:U12:plus2_0(+(1, n12888_0))) → *3_0, rt ∈ Ω(a·n128880 + n128880 + n1288802)

Generator Equations:
gen_tt:s:0':U11:U12:plus2_0(0) ⇔ tt
gen_tt:s:0':U11:U12:plus2_0(+(x, 1)) ⇔ s(gen_tt:s:0':U11:U12:plus2_0(x))

No more defined symbols left to analyse.

### (40) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n2) was proven with the following lemma:
a__U11(gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(n16876_0), gen_tt:s:0':U11:U12:plus2_0(c)) → *3_0, rt ∈ Ω(c·n168760 + n168760 + n1687602)

### (42) Obligation:

TRS:
Rules:
a__U11(tt, M, N) → a__U12(tt, M, N)
a__U12(tt, M, N) → s(a__plus(mark(N), mark(M)))
a__plus(N, 0') → mark(N)
a__plus(N, s(M)) → a__U11(tt, M, N)
mark(U11(X1, X2, X3)) → a__U11(mark(X1), X2, X3)
mark(U12(X1, X2, X3)) → a__U12(mark(X1), X2, X3)
mark(plus(X1, X2)) → a__plus(mark(X1), mark(X2))
mark(tt) → tt
mark(s(X)) → s(mark(X))
mark(0') → 0'
a__U11(X1, X2, X3) → U11(X1, X2, X3)
a__U12(X1, X2, X3) → U12(X1, X2, X3)
a__plus(X1, X2) → plus(X1, X2)

Types:
a__U11 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
tt :: tt:s:0':U11:U12:plus
a__U12 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
s :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
a__plus :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
mark :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
0' :: tt:s:0':U11:U12:plus
U11 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
U12 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
plus :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
hole_tt:s:0':U11:U12:plus1_0 :: tt:s:0':U11:U12:plus
gen_tt:s:0':U11:U12:plus2_0 :: Nat → tt:s:0':U11:U12:plus

Lemmas:
mark(gen_tt:s:0':U11:U12:plus2_0(n15871_0)) → gen_tt:s:0':U11:U12:plus2_0(n15871_0), rt ∈ Ω(1 + n158710)
a__U11(gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(n8498_0), gen_tt:s:0':U11:U12:plus2_0(c)) → *3_0, rt ∈ Ω(c·n84980 + n84980 + n849802)
a__U12(gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(n10562_0), gen_tt:s:0':U11:U12:plus2_0(c)) → *3_0, rt ∈ Ω(c·n105620 + n105620 + n1056202)
a__plus(gen_tt:s:0':U11:U12:plus2_0(a), gen_tt:s:0':U11:U12:plus2_0(+(1, n12888_0))) → *3_0, rt ∈ Ω(a·n128880 + n128880 + n1288802)

Generator Equations:
gen_tt:s:0':U11:U12:plus2_0(0) ⇔ tt
gen_tt:s:0':U11:U12:plus2_0(+(x, 1)) ⇔ s(gen_tt:s:0':U11:U12:plus2_0(x))

No more defined symbols left to analyse.

### (43) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n2) was proven with the following lemma:
a__U11(gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(n8498_0), gen_tt:s:0':U11:U12:plus2_0(c)) → *3_0, rt ∈ Ω(c·n84980 + n84980 + n849802)

### (45) Obligation:

TRS:
Rules:
a__U11(tt, M, N) → a__U12(tt, M, N)
a__U12(tt, M, N) → s(a__plus(mark(N), mark(M)))
a__plus(N, 0') → mark(N)
a__plus(N, s(M)) → a__U11(tt, M, N)
mark(U11(X1, X2, X3)) → a__U11(mark(X1), X2, X3)
mark(U12(X1, X2, X3)) → a__U12(mark(X1), X2, X3)
mark(plus(X1, X2)) → a__plus(mark(X1), mark(X2))
mark(tt) → tt
mark(s(X)) → s(mark(X))
mark(0') → 0'
a__U11(X1, X2, X3) → U11(X1, X2, X3)
a__U12(X1, X2, X3) → U12(X1, X2, X3)
a__plus(X1, X2) → plus(X1, X2)

Types:
a__U11 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
tt :: tt:s:0':U11:U12:plus
a__U12 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
s :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
a__plus :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
mark :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
0' :: tt:s:0':U11:U12:plus
U11 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
U12 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
plus :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
hole_tt:s:0':U11:U12:plus1_0 :: tt:s:0':U11:U12:plus
gen_tt:s:0':U11:U12:plus2_0 :: Nat → tt:s:0':U11:U12:plus

Lemmas:
mark(gen_tt:s:0':U11:U12:plus2_0(n7802_0)) → gen_tt:s:0':U11:U12:plus2_0(n7802_0), rt ∈ Ω(1 + n78020)
a__U11(gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(n8498_0), gen_tt:s:0':U11:U12:plus2_0(c)) → *3_0, rt ∈ Ω(c·n84980 + n84980 + n849802)
a__U12(gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(n10562_0), gen_tt:s:0':U11:U12:plus2_0(c)) → *3_0, rt ∈ Ω(c·n105620 + n105620 + n1056202)
a__plus(gen_tt:s:0':U11:U12:plus2_0(a), gen_tt:s:0':U11:U12:plus2_0(+(1, n12888_0))) → *3_0, rt ∈ Ω(a·n128880 + n128880 + n1288802)

Generator Equations:
gen_tt:s:0':U11:U12:plus2_0(0) ⇔ tt
gen_tt:s:0':U11:U12:plus2_0(+(x, 1)) ⇔ s(gen_tt:s:0':U11:U12:plus2_0(x))

No more defined symbols left to analyse.

### (46) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n2) was proven with the following lemma:
a__U11(gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(n8498_0), gen_tt:s:0':U11:U12:plus2_0(c)) → *3_0, rt ∈ Ω(c·n84980 + n84980 + n849802)

### (48) Obligation:

TRS:
Rules:
a__U11(tt, M, N) → a__U12(tt, M, N)
a__U12(tt, M, N) → s(a__plus(mark(N), mark(M)))
a__plus(N, 0') → mark(N)
a__plus(N, s(M)) → a__U11(tt, M, N)
mark(U11(X1, X2, X3)) → a__U11(mark(X1), X2, X3)
mark(U12(X1, X2, X3)) → a__U12(mark(X1), X2, X3)
mark(plus(X1, X2)) → a__plus(mark(X1), mark(X2))
mark(tt) → tt
mark(s(X)) → s(mark(X))
mark(0') → 0'
a__U11(X1, X2, X3) → U11(X1, X2, X3)
a__U12(X1, X2, X3) → U12(X1, X2, X3)
a__plus(X1, X2) → plus(X1, X2)

Types:
a__U11 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
tt :: tt:s:0':U11:U12:plus
a__U12 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
s :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
a__plus :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
mark :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
0' :: tt:s:0':U11:U12:plus
U11 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
U12 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
plus :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
hole_tt:s:0':U11:U12:plus1_0 :: tt:s:0':U11:U12:plus
gen_tt:s:0':U11:U12:plus2_0 :: Nat → tt:s:0':U11:U12:plus

Lemmas:
mark(gen_tt:s:0':U11:U12:plus2_0(n7802_0)) → gen_tt:s:0':U11:U12:plus2_0(n7802_0), rt ∈ Ω(1 + n78020)
a__U11(gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(n8498_0), gen_tt:s:0':U11:U12:plus2_0(c)) → *3_0, rt ∈ Ω(c·n84980 + n84980 + n849802)
a__U12(gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(n10562_0), gen_tt:s:0':U11:U12:plus2_0(c)) → *3_0, rt ∈ Ω(c·n105620 + n105620 + n1056202)

Generator Equations:
gen_tt:s:0':U11:U12:plus2_0(0) ⇔ tt
gen_tt:s:0':U11:U12:plus2_0(+(x, 1)) ⇔ s(gen_tt:s:0':U11:U12:plus2_0(x))

No more defined symbols left to analyse.

### (49) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n2) was proven with the following lemma:
a__U11(gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(n8498_0), gen_tt:s:0':U11:U12:plus2_0(c)) → *3_0, rt ∈ Ω(c·n84980 + n84980 + n849802)

### (51) Obligation:

TRS:
Rules:
a__U11(tt, M, N) → a__U12(tt, M, N)
a__U12(tt, M, N) → s(a__plus(mark(N), mark(M)))
a__plus(N, 0') → mark(N)
a__plus(N, s(M)) → a__U11(tt, M, N)
mark(U11(X1, X2, X3)) → a__U11(mark(X1), X2, X3)
mark(U12(X1, X2, X3)) → a__U12(mark(X1), X2, X3)
mark(plus(X1, X2)) → a__plus(mark(X1), mark(X2))
mark(tt) → tt
mark(s(X)) → s(mark(X))
mark(0') → 0'
a__U11(X1, X2, X3) → U11(X1, X2, X3)
a__U12(X1, X2, X3) → U12(X1, X2, X3)
a__plus(X1, X2) → plus(X1, X2)

Types:
a__U11 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
tt :: tt:s:0':U11:U12:plus
a__U12 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
s :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
a__plus :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
mark :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
0' :: tt:s:0':U11:U12:plus
U11 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
U12 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
plus :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
hole_tt:s:0':U11:U12:plus1_0 :: tt:s:0':U11:U12:plus
gen_tt:s:0':U11:U12:plus2_0 :: Nat → tt:s:0':U11:U12:plus

Lemmas:
mark(gen_tt:s:0':U11:U12:plus2_0(n7802_0)) → gen_tt:s:0':U11:U12:plus2_0(n7802_0), rt ∈ Ω(1 + n78020)
a__U11(gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(n8498_0), gen_tt:s:0':U11:U12:plus2_0(c)) → *3_0, rt ∈ Ω(c·n84980 + n84980 + n849802)

Generator Equations:
gen_tt:s:0':U11:U12:plus2_0(0) ⇔ tt
gen_tt:s:0':U11:U12:plus2_0(+(x, 1)) ⇔ s(gen_tt:s:0':U11:U12:plus2_0(x))

No more defined symbols left to analyse.

### (52) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n2) was proven with the following lemma:
a__U11(gen_tt:s:0':U11:U12:plus2_0(0), gen_tt:s:0':U11:U12:plus2_0(n8498_0), gen_tt:s:0':U11:U12:plus2_0(c)) → *3_0, rt ∈ Ω(c·n84980 + n84980 + n849802)

### (54) Obligation:

TRS:
Rules:
a__U11(tt, M, N) → a__U12(tt, M, N)
a__U12(tt, M, N) → s(a__plus(mark(N), mark(M)))
a__plus(N, 0') → mark(N)
a__plus(N, s(M)) → a__U11(tt, M, N)
mark(U11(X1, X2, X3)) → a__U11(mark(X1), X2, X3)
mark(U12(X1, X2, X3)) → a__U12(mark(X1), X2, X3)
mark(plus(X1, X2)) → a__plus(mark(X1), mark(X2))
mark(tt) → tt
mark(s(X)) → s(mark(X))
mark(0') → 0'
a__U11(X1, X2, X3) → U11(X1, X2, X3)
a__U12(X1, X2, X3) → U12(X1, X2, X3)
a__plus(X1, X2) → plus(X1, X2)

Types:
a__U11 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
tt :: tt:s:0':U11:U12:plus
a__U12 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
s :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
a__plus :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
mark :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
0' :: tt:s:0':U11:U12:plus
U11 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
U12 :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
plus :: tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus → tt:s:0':U11:U12:plus
hole_tt:s:0':U11:U12:plus1_0 :: tt:s:0':U11:U12:plus
gen_tt:s:0':U11:U12:plus2_0 :: Nat → tt:s:0':U11:U12:plus

Lemmas:
mark(gen_tt:s:0':U11:U12:plus2_0(n7802_0)) → gen_tt:s:0':U11:U12:plus2_0(n7802_0), rt ∈ Ω(1 + n78020)

Generator Equations:
gen_tt:s:0':U11:U12:plus2_0(0) ⇔ tt
gen_tt:s:0':U11:U12:plus2_0(+(x, 1)) ⇔ s(gen_tt:s:0':U11:U12:plus2_0(x))

No more defined symbols left to analyse.

### (55) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
mark(gen_tt:s:0':U11:U12:plus2_0(n7802_0)) → gen_tt:s:0':U11:U12:plus2_0(n7802_0), rt ∈ Ω(1 + n78020)